Optimal placement and sizing of the virtual power plant constrained to flexible-renewable energy proving in the smart distribution network. (February 2022) - Wu, Zhen-Zhen; Xu, Yi-Peng; Cheng, Zhi-Lin; Sun, Hong-Wei; Papari, Behnaz; Sajadi, Seyed Sajad; Qasim, Farah
Abstract: In this paper, optimal location and sizing of the flexi-renewable virtual power plants (FRVPPs) in the smart distribution network are aimed to achieve through proposing a bi-level optimization problem. In the upper-level formulation, the normalized summation of the network's voltage deviation function and annual operation cost is minimized, and it limiting to AC optimal power flow equations. The yearly operating and investment costs of renewable and flexible resources subjected to model of resources in FRVPP framework are minimized in the lower-level problem. Then, the bi-level problem is converted into a single-level formulation using Karush-Kuhn-Tucker approach to obtain the optimum solution through classical mathematical solvers. The scheme combines the adaptive robust optimization approach to consider uncertainties of renewable production, energy price, and demand. Ant-lion optimizer algorithm is utilized due to the nonlinearity of problem. In worst-case scenario, this process provides a robust optimal solution with estimated unique response conditions. A standard network is used for applying the suggested scheme. It is confirmed by the optimization results that the superiority and capabilities of the suggested method in ameliorating the economic and technical conditions of network while achieving the optimum size and location of FRVPP from an economic perspective.